1999
DOI: 10.1021/jp992751x
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Charge Transfer along a meso,meso-Linked Porphyrin Array

Abstract: Electroabsorption spectra of meso,meso-linked zinc porphyrin arrays doped in a PMMA polymer film have been measured with a field modulation spectroscopy, and the change in electric dipole moment (∆µ) and in molecular polarizability has been evaluated for the transition into each of the exciton splitting components of the Soret band. ∆µ following photoexcitation is non-zero in the oligomers, and the magnitude becomes larger with the increasing number of linked molecules, suggesting that photoinduced charge tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 16 publications
3
27
0
Order By: Relevance
“…Thus, even if the oscillator strength is small, it is regarded that the higher energy band still remains at around 450 nm and the lower energy band is shifted to red with gaining intensity. As previously noted, a slight charge-transfer character of the low-energy Soret band of 2 was revealed by the electronic absorption spectrum, [21] the absorption band at around 450 nm is attributed to the chargetransfer band, since the red-shifted absorption band at around 480 nm has strong excitonic nature. Thus, the RR bands that are enhanced only by the 457.9 nm laser line excitation are believed to arise from the charge-transfer character.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Thus, even if the oscillator strength is small, it is regarded that the higher energy band still remains at around 450 nm and the lower energy band is shifted to red with gaining intensity. As previously noted, a slight charge-transfer character of the low-energy Soret band of 2 was revealed by the electronic absorption spectrum, [21] the absorption band at around 450 nm is attributed to the chargetransfer band, since the red-shifted absorption band at around 480 nm has strong excitonic nature. Thus, the RR bands that are enhanced only by the 457.9 nm laser line excitation are believed to arise from the charge-transfer character.…”
supporting
confidence: 68%
“…This consideration is likely to be consistent with the recent results on the electronic absorption spectra of meso ± meso-linked diporphyrin doped in a PMMA polymer film; this indicates that there is a substantial change in electric dipole moment upon the transition at the split, lower energy Soret band. [21] Molecular orbital (MO) considerations: To understand the absorption spectra of the strapped diporphyrins, we started with a simple quantum chemistry consideration [24,25] and proceeded to more sophisticated calculations as described in the following. Initially, the strapped diporphyrins are modeled as a dimer of a simple unsubstituted porphin subunit with a variable dihedral angle (q) between the meso ± meso linkage as schematically displayed in Figure 10.…”
Section: Discussionmentioning
confidence: 99%
“…According to this interpretation, the singlet-singlet spectrum of an aggregate of BChle molecules changes, on account of transient environment-induced perturbation, from A() to AЈ(). The spectra of chlorosomes containing BChlc (22) and of the abovementioned meso,meso-linked porphyrin arrays (31) have been found to display strong electrochromism, and the changes in the absorbance of BChle recorded by us might well be induced by ionic photoproducts; however, the identification of the photoproduct which causes the perturbation must await further work, particularly the measurement of the Stark spectra of artificial aggregates. At present, we will simply denote the unidentified perturber by the symbol BChle ࠘ .…”
Section: Laser-induced Changes In Absorbancementioning
confidence: 89%
“…7 From spectroscopic measurements, it has been found that the Soret band of an array is split into two bands. 8 The split component located in the lower-energy region is further shifted downward with increases in the number of linked porphyrins, while the other split component located in the higher-energy region remains almost unchanged. These spectroscopic features, which are in rather good agreement with the prediction of the molecular exciton model, 10,22 have inspired researchers to study energy and charge-transfer processes in excited states of mesomeso-linked porphyrin arrays.…”
Section: Introductionmentioning
confidence: 94%
“…In the measurement of EA spectra, the porphyrin monomer and arrays were doped in a PMMA polymer film. 8 Since the dielectric constant of PMMA is as small as 3.6, we assume that the electrostatic interaction of a solute molecule with PMMA is negligible and that the solvation effects on the locations of excited states are also negligible. This assumption is justified by the fact that the absorption spectrum in a PMMA polymer film is nearly identical to that in a nonpolar solvent such as a benzene solution (of which the dielectric constant is 2.3).…”
Section: Field-induced Blue Shift Of the Lower Soret Bandmentioning
confidence: 99%